IMPLEMENTASI MURABAHAH BIL WAKALAH PRODUK PEMBIAYAAN BSI - M. Guffar Harahap; Haidir Haidir; Muhammad Hizbullah (JURNAL ILMIAH EDUNOMIKA, 2023)
Analysis is a work process of an effort to observe something in detail by describing its constituent components or compiling these components for further study. While the implementation can simply be interpreted as the implementation or application or expansion of activities that mutually adjust an activity that is planned and carried out seriously based on certain norms to achieve the objectives of the activity. Murabahah Bil Wakalah contract is a sale and purchase where the Islamic financial institution represents the purchase of the product to the customer, then after the product is obtained by the customer, it is given to the Islamic financial institution. The fatwa of the National Sharia Council regarding the granting of wakalah contracts in murabahah transactions is regulated in the fatwa of DSN-MUI/No.04/DSN/MUI/IV/2000, namely "if the bank wants to represent the customer to buy goods from a third party, the murabahah sale and purchase contract must carried out after the goods in principle become the property of the bank. Explicitly from this fatwa, it can be understood that the Wakalah contract must be carried out before the Murabahah contract, if in principle the goods must already belong to the bank, then the Wakalah must be carried out before the Murabahah contract is implemented. However, in practice, the Murabahah contract is signed (approved) by the customer at the same time as the Wakalah contract. Responding to this requires the efforts of various parties, Islamic economic scholars are expected to be present to review the contracts used. This study aims to see how successful Islamic banks are in implementing Murabah Bil Wakalah contracts on BSI implant financing products in Islamic banks and whether their implementation is in accordance with the DSN-MUI fatwa No.04/DSN/IV/2000 and DSN-MUI Fatwa No.10 . The research method used is a qualitative method and the instruments used by researchers in collecting data are in the form of observations (observations), interviews (intervews). Based on the results of the study, it turns out that the bank is not a pure seller who provides goods for customers' needs, but the bank represents the purchase of these goods to customers and customers buy goods from suppliers. The implementation starts from the murabahah contract first, then the bank makes the disbursement by transferring it to the customer's BSI account. On the same day, the bank (marketing) and the customer enter into a wakalah contract in which the sharia bank gives full power to the customer to buy the goods desired by the customer.